The Finnish Maritime Sector Inside the Cybersecurity Hurricane - Ahokas, Jenna (My University, 2018)
For a long time, maritime safety and security regulations have remodeled the operations of the international maritime sector. In recent years, there has emerged a new kind of security matter called cybersecurity, which has globally remodeled even further the operations of the maritime sector. Cybersecurity and its related key factors, cyberthreat and cyberattack, have showed new kind of threats and vulnerabilities of the maritime sector. Despite the growing number of researches of related to this topic, the overall awareness of the maritime cybersecurity occurs inadequate within the international maritime sector. The research question “How does the Finnish maritime sector experience cybersecurity?” aims at understanding the perceptions and opinions of the Finnish maritime sector’s key operators, which are port authorities, port operators and shipping companies, concerning cybersecurity. This thesis was conducted as a qualitative research which was built upon a comprehensive literature review and enhanced with in-depth interviews with the key operators of the Finnish maritime sector. The results show that the awareness within the Finnish maritime sector has increased, but there still occurs some differences between different maritime operators in terms of understanding the cybersecurity factors. The Finnish maritime operators have taken steps towards better cybersecurity, but there is still a great need for industry wide standards and practical level coordination. The NIS Directive has the chance to improve the cybersecurity operations even further and to simplify the concepts and procedures in terms of better cybersecurity situation.
Keywords: Maritime sector, safety, security, cybersecurity, cyberattack